Simone Staiger - Launch Website - International Center for Tropical Agriculture (2019)
Simone Staiger, Communications and MEL coordinator of SERVIR-Amazonia talks about the Program's communication channels and invites users to go to the Website https://servir.ciat.cgiar.org/